Evaluation of potential gene expression as early markers of insulin resistance and non-alcoholic fatty liver disease in the Indonesian population - Eunice Limantara; Felicia Kartawidjajaputra; Antonius Suwanto (Indonesian Journal of Biotechnology, 2018)
Early detection of insulin resistance (IR) or non-alcoholic fatty liver disease (NAFLD) is crucial to preventing future risks of developing chronic diseases. The Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), Liver Fat Score (LFS), and Fatty Liver Index (FLI) are generally employed to measure severity stages of IR and NAFLD. The study of gene expressions could explain the molecular mechanisms that occur early on in IR and NAFLD; thus providing potential early markers for both diseases. This study was conducted to evaluate the gene expressions that could potentially be early markers of IR and NAFLD. All participants (n = 21) had normal blood glucose and were categorized as without hepatosteatosis (n = 10), at higher risk of hepatosteatosis (n = 6), and hepatosteatosis (n = 5). Gene expression analysis was performed using the 2-∆∆CT relative quantification method. There were significant differences in galnt2 (p < 0.002) and sirt1 (p < 0.010) expression between the first and the third tertiles of HOMA-IR; and in ptpn1 (p < 0.012) expression between the first and the second tertiles of LFS. In conclusion, the expressions of galnt2 and sirt1 could be used as early markers of IR, while the expression of ptpn1 could be employed as an early marker of NAFLD.